Shear behavior of fiber-reinforced concrete hollow-core slabs under elevated temperatures - Nguyen, Hang T. N. (2022)
Experimental results of shear investigations on six hollow-core slabs with and without fibers cast by the extrusion method and tested under elevated temperatures are presented here. The purpose is to investigate shear behavior of precast/prestressed concrete hollow-core (PCHC) slabs using different types of fiber and fiber contents to resist fire effects. Three types of fiber including polypropylene (PP), hooked steel, and high-strength/straight steel fibers were employed. Two volume fractions of PP fibers (0.11 and 0.22%) and of steel fibers (0.51 and 0.89%) were examined. The effectiveness of PP fibers and steel fibers with different contents on structural performance of fire-exposed hollow-core slabs was quantified. Experimental results showed that the use of PP fibers increased resistance of concrete to explosive spalling, while resistance to load and elevated temperatures was substantially enhanced with the use of steel fibers. In addition, web-shear failure at an early stage of fire exposure was observed in all specimens without fibers and those with only PP fibers, exhibiting premature/brittle behavior. However, with the use of steel fibers, failure mode shifted from web-shear to flexural-shear or even flexural failure. Ductility and toughness of steel-fiber specimens subjected to elevated temperatures were also significantly enhanced. Test results from the experimental studies were then used to verify finite element (FE) models that simulated fire behavior of PCHC slabs with and without fibers. Good agreement between the test results and the FE models in terms of furnace temperature at failure, maximum deflection, and failure mode was obtained, thus verifying the numerical models. The verified FE models were then used to investigate web-shear mechanism of PCHC slabs exposed to fire. It is shown that temperature-induced tensile stresses in concrete webs (instead of temperature-induced reduction in strength of concrete and strands) governed web-shear behavior of PCHC slabs under elevated temperatures.